Peran Pemimpin Dalam Memotivasi Keprofesionalisme Pers di Kantor Persatuan Wartawan Indonesia (PWI) Kabupaten Deli - solidaritas Gea (Cattleya Darmaya Fortuna, 2021)
The success of an organization either in whole or in various groups in a particular organization depends on the quality of a leader in the organization concerned. Because in an organization the leader has a very dominant role in the success of the organization in carrying out various activities. The formulation of the problem in this study is